Molecular Mapping in Barley: Shifting from the Structural to the Functional Level - A Graner; T Thiel; H Zhang; E Potokina; M Prasad; D Perovic; R Kota; R K Varshney; U Scholz; I Grosse; N Stein (Czech Journal of Genetics and Plant Breeding, 2005)
As a resource for structural and functional barley genome analysis, more than 140 000 ESTs (expressed sequence tags) were generated from 22 cDNA libraries that yielded 25 224 tentative unigenes. About 50% of them belong to gene families. The size of the complete transcriptome is estimated to comprise between 35 000 and 75 000 genes. The barley EST collection is a rich source for the development of novel markers including SSRs (simple sequence repeats) and SNPs (single nucleotide polymorphisms). Several bioinformatic tools have been developed facilitating the computer-assisted analysis of EST databases for the presence of either SNPs or SSRs and the development of SNP-derived CAPS (cleaved amplified polymorphic sequences) markers. In an attempt to systematically map barley genes a high-density transcript map is under construction and presently comprises more than 1000 markers. This map is a gateway to comparative genomics with particular emphasis on the rice genome. 65% of the mapped ESTs showing a significant homology to rice ESTs were found to display a syntenic relationship between barley and rice. Thus, the barley EST resource facilitates the rapid and systematic transfer of genetic information from rice to barley and other Triticeae, which can readily be exploited for marker saturation of defined chromosome regions and their detailed comparison to rice. In the context of a functional genomics study, the complex trait "malting quality" is investigated using a barley cDNA array. By correlating the phenotypic malting trait data of selected barley lines with the corresponding expression profiles, a set of candidate genes was identified and further verified by genetic analysis.